Perfect for you - Terry, Candis (Terry, Candis. Sunshine Creek Vineyard novel., 2017)
Declan Kincade has spent so much time chasing success he<U+2019>s almost forgotten how to just live. Lately, though, his all-business routine has been thrown into disarray. Brooke Hastings is the best employee Dec<U+2019>s ever had: polished, capable, and intelligent. After four years, he<U+2019>s just realized that she<U+2019>s also smoking hot. But their working relationship is too valuable to stake on a fling, no matter how mind-bendingly pleasurable it promises to be . . . What<U+2019>s worse than never meeting the right man? Finding him, and then working side-by-side every day while he remains absolutely blind to your existence. That is, until one temptation-packed road trip changes everything. Teaching her gorgeous, driven boss how to cut loose and have fun is the toughest challenge Brooke<U+2019>s ever faced. But it<U+2019>s one that could give both of them exactly what they need, if Dec will take a chance on a perfect<U+2014>and perfectly unexpected<U+2014>love . . .